John Tyndall's religion: a fragment - Cantor, Geoffrey (Notes Rec R Soc Lond, 2015)
Both contemporaries and historians have focused on the high-profile 1874 Belfast Address in which John Tyndall was widely perceived as promulgating atheism. Although some historians have instead interpreted him as a pantheist or an agnostic, it is clear that any such labels do not accurately capture Tyndall's religious position throughout his life. By contrast, this paper seeks to chart Tyndall's religious journey from 1840 (when he was in his late teens) to the autumn of 1848 when he commenced his scientific studies at Marburg. Although he had been imbued with his father's stern conservative Irish Protestantism and opposition to Catholicism, as a youth he seems for a time to have been attracted to Methodism. Later, however, he questioned and rejected his father's religious views and was increasingly drawn to the more spiritual outlook of Ralph Waldo Emerson and Thomas Carlyle, along with a more radical attitude to politics.